Aluk To Dolo Versus Kristen - Kristanto, M.Th.; Yonathan Mangolo (KINAA: Jurnal Teologi, 2018)
Eventhough most of Toraja society especially the Bungin society are Christian but they often used the teaching of Aluk To Dolo (the way of Anchestors_ local animist belief) as references, guidelines and control tools for them.The influence of Aluk To Dolo is very visible in the way of their thinking and acting. The cause of Aluk To Dolo influence in the religiosity of Christian community in Bungin becomes the reason in conducted this research and it is employed qualitative method.The cause of Aluk To Dolo which still influence the religiosity of Christian community in Bungin is the teaching of Aluk To Dolo cannot be separated with the tradition which forceful weaving in the life of the community in Bungin from generation to generation so that it kept tight in memory and always appears in their thought and action.The other cause is the failed of the church to reject the role of Aluk To Dolo’s leader in the religious activities of the Christian community. It is also caused by the failure of tradition and religious leader to understand the principle of pemali pebullei aluk tu tau which becomes the principle of Toraja people for long time ago. Also, it is caused by the lack of the church role to carry out the Christian education program for the Christian community in Bungin so that it did not plaited the life of the Christian community in Bungin.